Predicting the impact of polypill use in a metabolic syndrome population: An effectiveness and cost-effectiveness analysis - Zomer, E.; Owen, A.; Magliano, D.; Ademi, Z.; Reid, Christopher; Liew, D. (2013)
Background: Individuals with metabolic syndrome (MetS) are at increased risk of cardiovascular disease (CVD), often requiring combination drug therapy for control of risk factors and subsequent risk reduction. This study aims to compare the long-term effectiveness and cost effectiveness of the polypill (a multi-component tablet), and its components (alone or in combination), in a MetS population. Methods and Results: A Markov state transition model, using individual subject data from the Australian Diabetes, Obesity and Lifestyle study, was constructed to simulate the effects of the treatment versus no treatment on CVD events, and costs over 10 years. In 1,991 individuals classified as MetS and free of existing diabetes mellitus or CVD, treatment with the polypill (or its components) was effective at reducing cardiovascular events [statin: 171, aspirin (actetylsalicylic acid): 201, antihypertensive: 186 per 1,000 individuals]. The more drug therapies employed the greater the reduction, with the polypill reducing up to 351 cardiovascular events per 10,000 individuals. Cost-effectiveness analyses were sensitive to drug treatment costs and effectiveness of treatment. At a cost of AUD$42 per person per annum, aspirin was considered cost saving. All other treatment strategies, including the polypill, were not cost effective. Conclusion: The polypill is likely to be effective in the reduction of cardiovascular events in a MetS population. It is, however, not cost effective. Nevertheless, in a high-risk population, among whom combination therapy is often prescribed, the polypill is likely to be more cost effective than antihypertensive therapy alone or dual therapy with a statin and antihypertensive combination. © 2013 Springer International Publishing Switzerland.